Changes in soil organic carbon and phosphorus status under three different land use systems in a tropical Ultisol - Nayanarangani, M.D.P.; Vitharana, U.W.A.; Kumaragamage, D.; Casson, N.J. (Geoderma Regional, 2025)
Anthropogenic land use systems and their management practices influence carbon (C) accumulation and storage and phosphorus (P) dynamics in soils. However, information on changes in soil organic C (SOC) reserves and P status in intensive annual cropping versus commercial perennial cropping systems is limited. This study examined the impact of long-term annual (vegetable) and perennial (tea) cultivation on the soil P and SOC status of a Tropical Ultisol compared to replanted forest land use. Surface (0–15 cm) soil samples obtained from forest- (25 ha), tea- (20 ha), and vegetable- (30 ha) lands within a micro-catchment were analyzed for available P (Mehlich 3-P), P fractions, SOC, permanganate oxidizable C (POxC, representing active SOC), and pH. Soils under long-term vegetable and tea with frequent applications of fertilizers had 78-fold and 7-fold greater available P (356.3 and 33.0 mg kg−1, respectively) than forest (4.6 mg kg−1) soils. Moreover, vegetable-grown soils had greater P concentrations in labile, moderately labile, and recalcitrant fractions than tea-grown and forest soils. Active C fraction in tea-grown soils (899 mg kg-1) was 2-fold than that of vegetable-grown soils (484 mg kg−1), but similar to forest soils (804 mg kg−1). The SOC in tea-grown and forest soils were similar (6.05 % and 5.84 %, respectively), but significantly higher than in vegetable-grown soil (4.50 %). Thus, soils from intensive annual cropping systems showed substantial P accumulations and lower SOC quantity and quality than perennial cropping systems, warranting better nutrient and SOC management and soil conservation measures to prevent further soil deterioration with annual cropping. [Display omitted]